2022
DOI: 10.1016/j.cmi.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of azole resistance in Aspergillus fumigatus complex isolates using MALDI-TOF mass spectrometry

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…The application of break points relies on accurate species-level identification; this has improved for yeasts with the increasing use of MALDI-TOF mass spectrometry systems, but for moulds is still dependent on local database content 58 . Direct detection of antifungal resistance with the MALDI-TOF platform for yeasts 59 and moulds 60 is an exciting new direction; however, MALDI-TOF is too costly for many centres (thereby complicating international resistance surveillance initiatives) and reliance on culturing increases the time to diagnosis.…”
Section: Diagnostics and Surveillancementioning
confidence: 99%
“…The application of break points relies on accurate species-level identification; this has improved for yeasts with the increasing use of MALDI-TOF mass spectrometry systems, but for moulds is still dependent on local database content 58 . Direct detection of antifungal resistance with the MALDI-TOF platform for yeasts 59 and moulds 60 is an exciting new direction; however, MALDI-TOF is too costly for many centres (thereby complicating international resistance surveillance initiatives) and reliance on culturing increases the time to diagnosis.…”
Section: Diagnostics and Surveillancementioning
confidence: 99%
“…Matrix‐assisted laser desorption/ionisation time‐of‐flight mass spectrometry (MALDI‐TOF MS) has been investigated as a tool for Aspergillus spp. identification including cryptic species 34–36 . In addition, Zvezdanova et al reported that MALDI‐TOF MS has the potential ability to discriminate between susceptible and azole‐resistant A. fumigatus sensu stricto isolates 36 .…”
Section: Discussionmentioning
confidence: 99%
“…identification including cryptic species 34–36 . In addition, Zvezdanova et al reported that MALDI‐TOF MS has the potential ability to discriminate between susceptible and azole‐resistant A. fumigatus sensu stricto isolates 36 . It is essential to improve the mass spectrometry database of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Next, 1µl of HCCA matrix solution (Bruker Daltonics) have been added to each spot. The MALDI-TOF spectra has been acquired in positive linear mode in the range of 2,000 to 20,000 Da, using default settings [31], although only data between 2,000-12,000 m/z [32], [33] has been used.…”
Section: A Isolates Selection and Processingmentioning
confidence: 99%